IMPLEMENTASI KEBIJAKAN SISTEM ZONASI DALAM PEMERATAAN PENDIDIKAN DI SMAN 1 KAMAL - Eni Syafitri; Agus Mahfud Fauzi (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2021)
The purpose of this study was to determine the implementation of education through the zoning system in Labang Bangkalan district. The zoning system as a form of government policy has the aim of equalizing education in Indonesia, including eliminating forms of discrimination in helping the needs and distribution of teachers, this policy is in accordance with Permendikbud Number 17 of 2017. Based on the reality in the field it is not yet appropriate, because there are still gaps such as obstruction of new students. to be able to enter the school they dream of because the quality of education in the Labang Bangkalan sub-district itself is not yet of good quality. Moreover, only by relying on the path of achievement where the opportunity is only 10% of the total applicants so that to make it happen requires collaboration with structures and communities such as educators, students, and the role of parents. This study uses qualitative methods because it is relevant to the research theme. The theory used as an analytical tool in this research is Structural Functional by Robert K Merton, which states that society as a system consists of various interrelated components. The reason the researchers took this theory was because it was related to the phenomenon of the application of the zoning system in which the system was viewed positively and negatively by the community. The results of the study show that there are still gaps in the implementation of zoning policies so that there is not yet equal distribution of education.Keyword: zoning system; education; discrimination.